Parasitic contamination of drinking water and its prevalence among handlers and sheep: Zainab A. Makawi and Mohammed Th. S. Al-Zubaidi - Al-Zubaidi, Mohammed Th. S. (The Iraqi Journal of Veterinary Medicine, 2018)
The current study was designed to determine the infection rate of intestinal protozoa in sheep and their handlers, and in their drinking water, in Wasit province, so as to study the relationship between contamination of drinking water with protozoal pathogen and infection in sheep and handlers in the period from the beginning of September 2015 to the end of February 2016. Two hundred eighty fecal samples were collected: (180) samples from sheep and 100 samples from human (50 handlers and 50 from non handlers), 50 drinking water samples were collected (18 samples; human tap water and RO bottled water and 32 samples river water). All samples were examined by conventional methods (direct moist smears, flotation with saturated sugar solution and stained with Modified acid fast, Giemsa and lugol's iodine ) The total infection rate in sheep, handlers and drinking water samples were 83.33%, 72%, 84.37% and 33.33% respectively. The result showed that drinking water samples of sheep and handlers were contaminated with protozoal oocysts or cysts of Cryptosporidium spp. (65.62%) (27.77 %), Giardia lamblia (6.25%) (0), Entamoeba spp (68.75%) (0), Eimeria spp (25%) (5.55%) and Buxtonella sulcata (40.62%)(0).